Influence of the Temperature as an Environmental Factor on the Electrophysical Behavior of Flexible Polymeric Luminescent Devices. (10th September 2014) - Aleksandrova, Mariya
Abstract : The effect of operational temperature on the electrophysical properties of polymer based electroluminescent structures is examined. For this purpose thin film of light-emitting semiconductor polyphenylenevinylene derivative is deposited between two indium-tin oxide (ITO) electrodes. DC current-voltage ( I-V ) characteristics of the fabricated devices ITO/polyphenylenevinylene derivative PPV-D/ITO are measured at varying ambient temperatures, ranging from room temperature (25°C) to 70°C. Several important electrical parameters like a trap factor, traps activation energy distribution, free carriers' density, trapped carriers density, and effective mobility are estimated from measured temperature dependent I-V curves. Such analysis of the charge transport process in polymer devices may give information needed for optimization of the existing structures.